Communicative Language Teaching in Aviation Vocational College Context: The Effect of Students’ Learning Perception and Attitude on Their EFL Learning Performance - Rochmawati, Laila; Sylvia, Tiara; Kusumayati, Lusiana Dewi; Silvia, Maulana Anifa (Universitas Muhammadiyah Yogyakarta, 2000)
This study examines the effect of learning perception and attitude on students' learning performance while implementing communicative language teaching (CLT) in a vocational college. The quantitative study used a survey research method with a cross-sectional design. 270 students participated in the study selected using a voluntarily random sampling technique. These research respondents were among those who had completed intermediate English classes with the amplification of the CLT method. Data were collected using a questionnaire with a four-point Likert's scaling method from very disagree (1) to very agree (4) (α = 0.843). The obtained data were analyzed using ANOVA with the assistance of IBM SPSS 25. Results showed a significant effect of learning perception (β = .890; F = 1018.849; p = 0.000) and attitude on students’ learning performance (β = .850; F = 698.468; p = 0.000). Among the two, learning attitude had been the more influential factor in students' learning performance during the implementation of CLT. This study suggested that CLT could be a catalyst for learning perception and attitude to elevate students' learning performance in the context of EFL teaching in vocational college.